Factors Influencing Green Purchase Intention among Generation Z consumers - Ng, Wei Ting; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2025)
Green products are particularly made to defend or improve the environment by preserving vitality and assets, whereas too minimizing or disposing of the era of poisonous squander, contamination, and hurtful substances. In Malaysia, driving companies have executed green activities to illustrate their devotion to natural supportability. The rapid pace of economic and industrial development has significantly increased individual purchasing power, resulting in greater environmental degradation. Nevertheless, many educated young consumers possess inadequate knowledge regarding green products. This study aims to assess the level of green purchase intention and to explore the relationship between green trust and green word of mouth on green purchase intention among Generation Z in East Coast Malaysia. A quantitative research methodology was utilized, with data gathered through a convenience sampling technique. The study included an overview of 365 members through a survey, and the information were analyzed utilizing SPSS computer program. Clear examination was utilized amid the information investigation stage. The discoveries demonstrated that both variables gotten tall scores based on central propensity measures. Relationship examination uncovered a positive relationship between all autonomous factors and green buy purposeful. The comes about concluded that green believe and green word of mouth displayed the most grounded affiliation with green buy deliberate.